(untitled) (International Seven Journal of Multidisciplinary, 2025)
Traditional Pedagogy is based on a mechanistic model that views the human being as a machine with a gear that dissociates relevant elements of the teaching-learning process, such as cognition, affectivity, context, didactic contract, student, and teacher. These are elements that do not interact with each other and conceive of the locus as a space for the transmission of knowledge accumulated over generations and intended to be transmitted vertically by the totemic figure of the teacher, who holds all knowledge. In this article, we revisit the assumptions of Traditional Pedagogy, discussing the role of the teacher, the student, the worldview, how the relationships between teaching and learning occur, and their implications for the work of professionals in the fields of psychology and education, respectively.